COMBINATION OF BASIC SCIENTIFIC RESEARCH WITH ENGINEERING DEVELOPMENTS - Sergey A. Mikhailov (Высшее образование в России)
Abstract. On the threshold of the 85th anniversary of Kazan Aviation Institute (today KNRTUBKAI) the goals and tasks of research activity conducted at the university are analyzed. It is noted that the specific character of scientific and educational process is distinguished by a combination of basic and applied scientific research with experimental-design developments, created in close ties with the industry. The aim of establishing an Institute in 1932 was to provide the aircraft industry with the skilled engineers. Today a priority of KNRTU-KAI scientific development is professional and technological support for high-tech mechanical engineering. To implement the given strategy the university has created engineering centers equipped by high-tech facilities up to the latest world standards as well as enterprise-based departments. The university is actively involved in implementing federal special-purpose programs, grant programs of the RF government, the RF Ministry for Education and Science and others.